Comparative evaluation of coagulase-negative staphylococci (CoNS) adherence to acrylic by a static method and a parallel-plate flow dynamic method - Cerca, Nuno (2004)
The main goal of this work was to evaluate the adhesion to acrylic of several clinical strains of Staphylococcus epidermidis and Staphylococcus haemolyticus using both static and dynamic adhesion methods, and to compare the results obtained with these two methods. Adhesion was evaluated using the static slide method with different washing procedures, and the parallel plate flow chamber method. The extent of S. epidermidis adhesion, assessed by both methods, was greater than that of S. haemolyticus. The number of bacteria which adhered using the static method was lower than that using the dynamic method. It was found that the simple static method, when performed with an accurate washing procedure, can be as effective as the dynamic flow method for assessing differences in the adherence capacity of strains. Although the dynamic flow method yielded more overall information, its greater complexity and cost may not always justify its use for certain experimental comparisons. This investigation has shown that simple static adhesion methods, when performed accurately, can be used to evaluate differences in adhesion capacity.